PELATIHAN ETIKA DAN KOMUNIKASI DIGITAL UNTUK REMAJA DI PONDOK PESANTREN SYAMSUL HUDA BATAM - Hendri Kremer; Arwin Ramly; Sasa Ani Arnomo (ASOSIASI IDEBAHASA KEPRI, 2026)
The increasing popularity of social networking applications among the younger generation raises crucial issues regarding digital ethics and responsible communicative behavior, educational efforts are needed through various educational channels. This community service program is designed to strengthen the understanding and ability of teenagers in managing social media platforms ethically and responsibly through a specific training program implemented at the Syamsul Huda Islamic Boarding School in Batam. This activity involved 25 school participants with a participatory method consisting of six phases, namely: counseling, interaction-based training, digital content workshop sessions, group forums, practical sessions, and assessments, complemented by pre-test and post-test measurements to evaluate the program's success. Evaluation data shows a 78% increase in understanding of digital ethics and a 65% increase in communication skills through social media platforms, while the level of participant satisfaction with the program reached 92% based on the results of a questionnaire conducted after the training. This training program also plays an important role in improving the quality of social media applications among teenagers and helping them develop wiser attitudes in digital interactions, in line with the initiative to form a digital generation that has ethical integrity and is able to communicate constructively.